Immunometabolism in fungal infections: the need to eat to compete. (December 2020) - Weerasinghe, Harshini; Traven, Ana
Abstract : Immune cells, including macrophages and monocytes, remodel their metabolism and have specific nutritional needs when dealing with microbial pathogens. While we are just beginning to understand immunometabolism in fungal infections, emerging themes include recognition of fungal cell surface molecule driving metabolic remodelling to increase glycolysis, the critical role of glycolysis in the production of antifungal cytokines and fungicidal effector molecules, and the need for maintaining host glucose homeostasis to defeat fungal infections. A crosstalk between host and pathogen metabolic pathways determines the fate of immune cells and fungi when they interact. Thus, immunometabolic interactions offer potential for innovation in antifungal treatments in the future. For this to become a reality, we must decipher the mechanisms by which diverse fungal pathogens activate and manipulate immunometabolism.